Effects of adhesive and loading directions on the load-carrying capacity of V-nails - Taghiyari, Hamid R.; Ghofrani, Mohammad; Arbabi Ghamsari, Farzad (Maderas. Ciencia y Tecnología, 2017)
Effects of tensile and compression loading on the overall strength of two miter frame corner joints, namely V-nail and dovetail joints, with and without adhesive were studied for medium-density fiberboard and particleboard. Two sizes of V-nails were chosen, sizes 7 and 10. Tensile and compression load-carrying capacity values were measured on the internal and external corners of the joints. Results showed that both wood-composites had greater load-carrying capacities for compression stress in comparison to tensile stress. Medium-density fiberboard demonstrated higher strength compared to particleboard specimens because of its higher compactness of fibers and more integrity in the composite matrix. Application of adhesive resulted in a significant increase in the strength of all joints and both composites. The increase in medium-density fiberboard was significantly higher in comparison to particleboard because lower permeability in medium-density fiberboard did not let adhesive to be uselessly penetrated into the texture. In particleboard specimens, however, adhesive penetrated into the voids and spaces in the composite, and the adhesive line was weakened between the surfaces of the composite bodies. It was concluded that V-nails are recommended for craftsmen in case adhesive is used. However, dovetail joints provide higher strength if the production process necessitates not to use adhesive in joints.